Ketepatan Menjelaskan Nasikh , Mansukh Pada Ayat Al-Qur’an Dan Hadis - Azriel Restu Fajar; Muhammad Jefri Wahyudi; Arif Rahman Al Havit (CV. ITTC INDONESIA, 2025)
This study aims to analyze the accuracy of explaining the concepts of nasikh and mansukh in Qur'anic verses and hadith, both from classical and contemporary perspectives. Nasikh means a verse or hadith that abolishes previous laws, while mansukh is a law that is abolished. This concept holds an important position in the science of tafsir and ushul fiqh because it is directly related to the establishment of Islamic law (istinbat al-ahkam) and understanding the meaning of revelation as a whole. This study uses a descriptive qualitative approach with a library research method, examining classical literature such as Al-Itqan fi Ulum al-Qur'an by As-Suyuthi and contemporary works such as Quraish Shihab (2020), Abdullah Saeed (2016), and Abou El Fadl (2019). The results show that nasikh and mansukh are not a form of contradiction in revelation, but rather a manifestation of Divine wisdom in adapting law to the social and spiritual conditions of the people. Legal changes are pedagogical and gradual, reflecting the principles of tadarruj fi al-tasyri' (gradually establishing the law) and maqashid al-syari'ah (the goals of the sharia). In the contemporary context, understanding Nasakh-Mansukh needs to be placed within a contextual hermeneutic framework so as not to cause misunderstandings in interpreting the text. This research confirms that the accuracy of explaining nasikh-mansukh has a strategic role in modern Islamic education, especially in integrating the moral, social and historical values ​​of Islamic law into the study of tafsir and hadith